Automotive Salespeople Performance: Political Skill, Relationship Building, and Deviance - Abigail Gracia; Yokie Radnan Kristiyono (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
This study explores the relationship between political skill, customer-relationship-building competence, customer-oriented selling, and customer-directed deviance, and investigates whether these relationships affect the sales performance of PT. Astra International Tbk. This study included 220 automotive salespeople as sample using nonprobability sampling, purposive sampling method technique, with various showroom branches of PT Astra International – Tbk’s automotive dealerships as the study’s setting. Structural Equation Modeling is used to test the study’s hypotheses. Results suggest that political skill positively affects customer-relationship-building competence and sales performance yet negatively affects customer-oriented selling and customer-directed deviance. Customer-relationship-building competence positively affects sales performance yet negatively affects customer-oriented selling and customer-directed deviance. Customer-oriented selling positively affects customer-directed deviance and customer-directed deviance negatively affects sales performance. Theoretical and managerial implications for future research are provided.